High tumor mutational burden assessed through next-generation sequencing predicts favorable survival in microsatellite stable metastatic colon cancer patients - Annabella Di Mauro; Mariachiara Santorsola; Giovanni Savarese; Roberto Sirica; Monica Ianniello; Alessia Maria Cossu; Anna Ceccarelli; Francesco Sabbatino; Marco Bocchetti; Anna Chiara Carratù; Francesca Pentimalli; Gerardo Ferrara; et al. (Journal of Translational Medicine)
Abstract Background Microsatellite instability (MSI) is a well-established predictive biomarker for immune checkpoint inhibitor (ICI) response in metastatic colon cancer. Both high MSI and tumor mutational burden (TMB) are markers of genomic instability. However, the prognostic and predictive value of TMB in patients with microsatellite stable (MSS) tumors remains unclear. Methods We evaluated the prognostic significance of TMB levels in MSS metastatic colon cancer patients undergoing standard treatments. Tumor responses were assessed using RECIST v1.1 criteria. Comprehensive clinical and molecular profiling was conducted, including next-generation sequencing (NGS) for TMB evaluation with the TruSight Oncology® kit. Overall survival (OS) was the primary endpoint. Multivariate Cox regression analysis was utilized to assess the relationship among potential prognostic factors. Results Among 102 MSS metastatic colon cancer patients, high TMB (> 10 mut/mb) was associated with a significantly longer median OS compared to low TMB (70.0 vs 45.0 months, respectively; HR: 0.45; 95% CIs 0.21 to 0.96; P = 0.0396). Multivariate analysis, adjusting for age, gender, number of metastatic sites, response to first-line chemotherapy, RAS mutational status, and liver involvement, identified TMB as an independent prognostic factor, along with response to first-line chemotherapy. Conclusions Our results highlight the prognostic significance of TMB in MSS metastatic colon cancer patients, suggesting its potential role in patient stratification and treatment decision-making.